A fast and spatialized urban weather generator for long-term urban studies at the city-scale - Le Bras, Julien; Masson, Valéry (Frontiers in Earth Science, 2015)
In order to make urban climate predictions at the city-scale and on long term experiment accessible to communities such as building engineers or urban planner, a method to calculate meteorological forcing for surface models is presented. This method is computed with weather data files from an operational measurement station outside of the city. The model, called the spatialized urban weather generator (SUWG) calculates the temperature field above the urban canopy level with an energy budget for each volume of the boundary layer considered and 2D lagrangian advection model in order to take wind advection into account.This method has multiple advantages. First, the files from operational weather stations can easily be found for a lot of cities, in most case in airports. Second, the calculated urban heat island (UHI) can be influenced by urban planning scenarios. The method has been validated with an operational weather station network giving temperatures over the region of Paris and by comparing the SUWG simulations to a complete high resolution atmospheric simulation (MesoNH model) done over the Paris region at 2km of resolution during years 2010 and 2011. The full atmospheric model and the SUWG give comparable results with comparison to the data over the period studied for each urban operational station.